On the existence of east African natural Megafocus of Yersinia pestis, Phylogenetic Lineage 1.ANT of the Antique Biovar of the Main Subspecies: epidemic Activity, spatial and Biocenotic structure - N. V. Popov; I. V. Kutyrev; A. V. Ivanova; K. A. Nikiforov; A. A. Zubova; Ya. A. Neishtadt; A. V. Boiko; E. V. Kuklev; V. P. Toporkov (Проблемы особо опасных инфекций, 2024)
The obtained results of the epidemiological, epizootiological, and phylogenetic data analysis suggest that the territory of the East African plateau is a one natural mega-focus of Yersinia pestis belonging to antique biovar 1.ANT of the main subspecies. The circulation of various genovariants (1.ANT1, 1.ANT2, 1.ANT3) of Y. pestis, antique biovar of the main subspecies, occurs in populations of various species of wild-living and semi-synanthropic rats and their specific ectoparasites. Within the boundaries of the established areal of antique biovar 1.ANT of the main subspecies of Y. pestis epizootic manifestations are confined to densely populated areas of the Democratic Republic of the Congo (DRC), Uganda, Kenya, Tanzania, Zambia and Malawi. Potentially plague enzootic regions should include the territories of Rwanda and Burundi, as well as the northern regions of Mozambique. In 2000–2024, more than 15.5 thousand cases of plague infection were registered in East African countries (DRC, Zambia, Malawi, Tanzania, Uganda), which is 54 % of the total number of cases on the African continent. The maximum epidemic activity (on average 1,326 people per year) of the East African megafocus was noted in 2000–2009. In 2010–2019, the incidence rates in the DRC, Uganda, and Tanzania decreased significantly (to an average of 103 people per year), and no cases of plague infection were detected in Zambia and Malawi. In 2020–2024, epidemic complications of plague continued to be recorded only in the territory of the DRC. The persistence of constant risks of infection is determined by the high population density and intensity of contacts between the rural population and the natural-focal complexes of the East African plateau. The high incidence of plague is also due to the development of outbreaks of anthroponotic bubonic plague associated with the abundance of Pulex irritans fleas in rural areas.